Programa trabaja Perú y la inserción laboral de la población femenina rural en el Perú 2012-2019 - Sanchez Sanchez, Rosa Victoria (2023)
This magisterial thesis considered Peruvian women from rural areas who have fewer possibilities of accessing the labor market due to educational, social and cultural limitations as study population, for which they require support from the public sector to insert themselves into economic activities. One of the state supports is the Trabaja Peru Program created in 2011. Thus, the applied methodology was quantitative, correlational level and non-experimental design. The work determined using the Pearson correlation coefficient at 90% confidence, that the amounts accrued by the Program in charge of the national government are directly related to the labor insertion of the rural female population 2012-2019 by 68.62%. Otherwise, no relationship was found between the second variable mentioned and the amounts accrued by regional and local governments.